BIOLOGY OF SUGAR BEET VARIETIES, PESTS, DISEASES AND MEASURES TO CONTROL THEM (British Journal of Global Ecology and Sustainable Development, 2024)
Information is provided on the biology of sugar beets, methods of growing them, as well as pests and diseases. Methods for protecting sugar beets from insects and diseases are described. Data from scientific studies of beet varieties are also presented.